STAT3 gene polymorphism in chronic obstructive pulmonary disease - Wang, J; Dai, N; Cheng, D-H; Gao, J-Y; Zheng, J-Q; Liu, Z-G (European review for medical and pharmacological sciences, 2020)
The aim of this study was to explore the correlation between rs8069115, rs41289087, and rs11079042 polymorphisms of the signal transducer and activator of transcription 3 (STAT3) gene and chronic obstructive pulmonary disease (COPD). A total of 200 patients diagnosed with COPD were enrolled in the disease group. Meanwhile, 200 normal subjects were selected as the control group. Peripheral blood was collected from subjects in the disease group and control group. Subsequently, nucleated cells were isolated for determination of STAT3 gene polymorphisms. Quantitative Polymerase Chain Reaction (qPCR) was utilized to detect the expression level of STAT3. Samples from 12 patients with differences in STAT3 haplotypes and 12 cases with no difference were collected and treated with transcriptome sequencing to analyze pathways enriched with differentially expressed genes. There were statistically significant differences in allele distributions at rs8069115 between the disease group and control group (p=0.000), and the allele frequency of G was higher in disease group. Genotype distributions of rs8069115 (p=0.000) and rs41289087 (p=0.000) of the STAT3 gene in disease group were significantly different in comparison with the control group. The frequency of rs8069115 GG genotype was remarkably higher, while the frequency of rs41289087 TG genotype was lower in the disease group (p<0.05). In addition, compared with the control group, the distributions of the dominant model (p=0.002) and recessive model (p=0.004) of rs8069115 of the STAT3 gene were markedly different in the disease group. A significantly higher frequency of dominant model GG+GA and lower frequency of recessive model GA+AA were observed at rs8069115 in the disease group (p<0.05). Moreover, the haplotype distributions of AGC (p=0.002), ATC (p=0.001), GTA (p=0.010), and GTC (p=0.035) at rs8069115, rs41289087, and rs11079042 were different between the disease group and control group. Besides, rs8069115 locus and rs11079042 locus were linked to each other (D'=0.523). There was a remarkable association between rs11079042 polymorphism of the STAT3 gene and gene expression (p<0.05). STAT3 was highly expressed in patients with genotype CC (p<0.05). Furthermore, changes in transcriptome levels among different haplotype populations (haplotype with different distributions vs. haplotype with no difference in distribution) were analyzed. The results demonstrated that multiple pathways, such as ECM-receptor interactions, cell cycle checkpoints, and protein processing were notably enriched (p<0.05). According to our results, we confirmed that the polymorphisms (rs8069115, rs41289087, and rs11079042) of STAT3 gene are noticeably correlated with the occurrence and progression of COPD.